Job satisfaction and its relationship to organizational loyalty - A field study on a group of executives at the Central Equipment Directorate at the Port of Algiers - tebani, ahlem; bouamama, smain (Journal of Social Sciences and Humanities, 2021)
The job satisfaction and the loyalty with in the organization are subjects that need to be researched and studied from time to time by leaders and managers and those who are intersted in manageri al developement in the work place .This study was done to determine how far the job satisfaction contributes to orgnizational loyalty. Based on a field study achieved on a sample of 60 executives in the port of Algiers, whileusing the descriptive approach, weused the data collection on the first measures of the job satisfaction and the second to measure the loyalty of the organization. The results of the study showed a lack of astatiscally significantcor relation between the indicators of the job satisfaction and the organizational loyalty.